(untitled) - Best, Roger J (London, 1997)
A central theme of this book is a discernible relationship between market orientation, customer satisfaction, and probability. This book is built around a commiment to a market orientation and the market management practices needed to create a superior value for customers and profitable growth for a business. A common thrust throughout this book is the goal of building market-based strategies that positively impact customer value and probability
Keywords: Marketing; Management